Al-Ma’un Values as the Basis for Educational Humanization at SMK Muhammadiyah 1 Bantul - Sofiani, Isma Yulia; Perawironegoro, Djamaluddin; Kholis, Nur; Hopid, Abdul; Masduki, Yusron; Pradita, Ega Krisna (Universitas Muhammadiyah Malang, 2026)
This research is driven by the phenomenon of dehumanization in contemporary education, which tends to overemphasize cognitive aspects, technical skills, and mechanical productivity for industrial needs, thereby neglecting the affective, spiritual, and social dimensions of students. Vocational schools (SMK) face a unique challenge in balancing industrial competence demands with the formation of noble character and social concern. SMK Muhammadiyah 1 Bantul (MUSABA) seeks to address this by integrating Al-Ma’un theology as a foundation for humanizing education. The objectives of this research are to describe and analyze the implementation of Al-Ma’un values at SMK Muhammadiyah 1 Bantul, to interpret the practices of educational humanization at the school, and to examine the integrative model of Al-Ma’un values as a philosophical and operational basis for developing humanistic education. This study is qualitative research using a case study approach. Data were collected through in-depth interviews with the Principal, ISMUBA teachers, and students, direct observation of school interactions and social activities, and documentation of school policies. Data analysis followed the interactive model by Miles, Huberman, and Saldaña, involving data reduction, data display, and conclusion drawing. The research findings indicate that: (1) The implementation of Al-Ma’un values at MUSABA is manifested through social concern (ta’awun), sincerity, and siding with the marginalized (mustad’afin), which are integrated into the school’s vision, mission, and organizational culture. (2) Educational humanization is practiced through inclusive policies, dialogic pedagogy, and a school environment that functions as a “second home” without violence or discrimination. (3) Al-Ma’un values serve as the basis for humanization by transforming the paradigm of students from “industrial objects” to “God’s mandates” (Amanah), realized through spiritual-humanist counseling and scholarship programs (Lazismu) to empower those in need. The conclusion of this research confirms that Al-Ma’un theology has successfully transformed vocational education at SMK Muhammadiyah 1 Bantul into an institution that produces graduates who are not only technically skilled but also possess strong social character and humanistic values.